Respuesta :
Answer:
answer is A for APEX..
Step-by-step explanation:
The function f(x) = [tex]x^{2} -4x+4[/tex] is shifted 3 units to the right to create
g(x) = [tex](x-3)^{2}-4(x-3)+4[/tex] .
What is shifting of a function?
A shift is a rigid translation in that it does not change the shape or size of the graph of the function. All that a shift will do is change the location of the graph. A vertical shift adds/subtracts a constant to/from every y-coordinate while leaving the x-coordinate unchanged.
Given
f(x) = [tex]x^{2} -4x+4[/tex]
The function f(x) = x2 – 4x + 4 is shifted 3 units to the right to create g(x).
If the function is shifted to the left it is going to plus(+).
If the function is shifted to the right it is going to minus(-).
So, x = x - 3
g(x) = [tex](x-3)^{2}-4(x-3)+4[/tex]
The function f(x) = [tex]x^{2} -4x+4[/tex] is shifted 3 units to the right to create
g(x) = [tex](x-3)^{2}-4(x-3)+4[/tex] .
Option A is correct.
Find out more information about shift here
https://brainly.com/question/11943912
#SPJ2